2021
DOI: 10.1007/s12529-020-09950-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Sleep: Associations with Shifts in Circulating Cytokines and Emotional Distress in a Cancer Survivor Population

Abstract: Background Sleep disturbances are associated with numerous mood disorders. Similarly, anxiety and depression are associated with modulation of the psychoneuroimmune (PNI) axis. This study hypothesized that changes in both monitored and self-reported measures of sleep would relate to changes in circulating cytokine levels in an emotionally distressed population of cervical cancer survivors. Methods Biospecimens, patient-reported outcome (PRO) measures, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Indeed, plasma concentrations of pro-inflammatory biomarkers were found to increase several fold during oncological therapy but only in patients whose sleep quality concurrently deteriorated during this period. These findings are in line with previous studies showing that pro-inflammatory biomarkers such as IL-1b, IL-2, IL-6, IL-12, and TNF-a increase in cancer patients following a period of sleep disruption ( Mantovani et al, 2008 ; Jensen et al, 2021 ; Tucker et al, 2021 ). Surprisingly, patients reporting improved sleep quality during oncological therapy exhibited reduced plasma levels of pro-inflammatory cytokines clearly demonstrating that sleep disruption rather than cytostatic or cytotoxic therapy is driving the increased systemic inflammation observed in these patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, plasma concentrations of pro-inflammatory biomarkers were found to increase several fold during oncological therapy but only in patients whose sleep quality concurrently deteriorated during this period. These findings are in line with previous studies showing that pro-inflammatory biomarkers such as IL-1b, IL-2, IL-6, IL-12, and TNF-a increase in cancer patients following a period of sleep disruption ( Mantovani et al, 2008 ; Jensen et al, 2021 ; Tucker et al, 2021 ). Surprisingly, patients reporting improved sleep quality during oncological therapy exhibited reduced plasma levels of pro-inflammatory cytokines clearly demonstrating that sleep disruption rather than cytostatic or cytotoxic therapy is driving the increased systemic inflammation observed in these patients.…”
Section: Discussionsupporting
confidence: 93%
“…In such studies, survivors of childhood ALL exhibiting poor sleep were found to have elevated plasma levels of IL-6, IL1b and CRP ( Cheung et al, 2017 ), and elevated IL-6 levels were correlated to poor sleep in non-small cell lung cancer patients receiving chemoradiotherapy ( Wang et al, 2010 ). Tucker et al found that IL-2, IL-1b, and IL-6 were upregulated in cancer survivors exhibiting reduced sleep duration based on actigraph measurements, but not in patients with self-reported sleep disruption where instead IL-10 were found to be upregulated ( Tucker et al, 2021 ). Here we took a different approach by keeping the inclusion criteria broad: All cancer patients with performance status 0 or 1, scheduled for oncological therapy were invited to participate regardless of age, gender, cancer type, tumor stage, type of planned oncological therapy, pre-treatment status, prior surgery, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection tool uses a questionnaire body image and Depression Anxiety Stress Scale (DASS). The result of Body image is categorized as good (mean ≥) and poor (mean <23) while DASS is categorized as normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33) and extreme severe (≥ 34). Body image questionnaire is valid (0,353-0,754) and reliable (Cronbach's alpha 0.483).…”
Section: Discussionmentioning
confidence: 99%
“…27 It will cause the increasing sleep time or decrease in sleep problems corresponded with a reduction in self-reported emotional distress and attenuation of pro-inflammatory, Th2, and counter-regulatory cytokines. 28 The body images are correlated to the stress level of cervical cancer patients who received chemotherapy in the Gynecology Centers of Dr. Kariadi General Hospital Medical Center. Patients' average body image was categorized as good but those with the lowest score thought that the disease, along with the chemotherapy, resulted in worse body condition, hair loss, weakness, fatigue, loss of appetite, and less social contact as the loss of confidence regarding the physical changes.…”
Section: Discussionmentioning
confidence: 99%
“…83 Major depression leads to severe disorders in the personal, social and employment life of the affected person and affects the person's health. 84 Depression has different types with different intensities, and therefore complications such as inflammation will be different in these patients. In this study, we review major depression and the inflammatory factor IL-2.…”
Section: Discussionmentioning
confidence: 99%